Thinking and acting globally and locally: Developing transnational social work practices in Belgium. Issue 2 (4th May 2017) - Withaeckx, Sophie; Schrooten, Mieke; Geldof, Dirk
Abstract: In societies characterized by globalization and increasing mobility, social workers are more often confronted with transmigrants: people who move multiple times, combine complex migration trajectories, and whose social lives are shaped in various sites. The growing complexity of these mobile clients' needs calls for a paradigm shift in social work. Social workers can no longer suffice with locally grounded, one-nation state solutions to their transnational clients' problems, but will need to cross borders both literally and figuratively. Concepts of international and transnational social work have been formulated to reflect the challenges posed by globalization and increasing mobility, remain however still underdeveloped, and the concrete shapes transnational social work practice remain as yet under-researched. Based on a qualitative research on social work with transmigrants, this paper describes emerging practices of transnational social work in Belgium. We argue that transnational social work is as much an attitude as an actual practice, as the development of a transnational awareness serves as an important precondition for recognizing transmigrants' welfare needs. The realization of the much-needed paradigm shift calls, however, for a firm incorporation of this awareness on all levels of social work practice and in its still locally directed policy frames.